1990
DOI: 10.2500/105065890782021033
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Paranasal Sinus Surgery: Results

Abstract: From June 1986 until January 1988, 165 patients underwent endoscopic paranasal sinus surgery, and the results were evaluated. Surgery was performed for a variety of different indications, and 69% of the patients had had prior nasal surgery. Preoperative findings on nasal endoscopy and tomography are discussed. The subjective result, or the patient's opinion of the operation, was considered good in 51%, moderate in 22%, and poor in 27% of patients. Postoperative nasal endoscopy showed a good result for 63% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 12 publications
2
38
0
Order By: Relevance
“…The highest report of perfect cavities was 63%. However, this series used non-validated endoscopy, the patient population included only 22% CRSwNP patients and surgical indications included headache and nasal obstruction 15 . It is also important to note that CRSwNP patients in our series had a number of significant differences from CRSsNP patients, including number of prior surgeries, asthma prevalence and aspirin tolerance (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The highest report of perfect cavities was 63%. However, this series used non-validated endoscopy, the patient population included only 22% CRSwNP patients and surgical indications included headache and nasal obstruction 15 . It is also important to note that CRSwNP patients in our series had a number of significant differences from CRSsNP patients, including number of prior surgeries, asthma prevalence and aspirin tolerance (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Another study also showed that nasal obstruction was more likely to be associated with CT scan findings 7. Symptoms have been shown to not correlate well with nasal endoscopy in preoperative CRS patients 15, 16…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients in Kennedy's study continued to use topical steroids postoperatively. Vleming et al showed a 52% persistence of endoscopic disease in spite of subjective good results 31 . Based on this, we believe that chronic sinusitis is basically a mucociliary clearance abnormality and that the obstructive element is either the only or one of the aggravating factors.…”
Section: Discussionmentioning
confidence: 56%